U.S. stock market P/E ratios, structural breaks, and long-term stock returns - Baek, Chung; Lee, Ingyu (Journal of Business Economics and Management, 2018)
Our study investigates structural changes in the market P/E ratio and shows how structural changes affect long-term stock market returns. Using the cumulative sum control chart and the Bai-Perron algorithm, we identify multiple structural breakpoints in the market P/E ratio and find that those structural changes are significantly perceived over the long run. Unlike previous studies that do not consider structural changes, our study is the first one that shows how structural changes asymmetrically influence long-term stock returns depending on the high or low P/E period. This implies that structural changes in the market P/E ratio play an important role in explaining long-term stock returns. We propose that structural changes should be taken into account in some manner to establish the relationship between P/E ratios and long-term stock returns.